Penerapan Projek Penguatan Profil Pelajar Pancasila Dengan Tema Kewirausahaan Pada SMA Negeri 2 Tarakan - Rahmi Nur Islami; Nurjannatul Hasanah (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
The project to strengthen the Pancasila or P5 student profile is one part of the Merdeka curriculum implemented in schools. SMA Negeri 2 Tarakan implements P5 by taking the theme of entrepreneurship. Entrepreneurship is the process of identifying, developing, and bringing a vision to run something in life. Activity P5 aims to determine and analyze the effectiveness of the Pancasila Student Profile Strengthening Project in fostering students' entrepreneurial spirit.